2018
DOI: 10.1007/s40121-018-0198-x
|View full text |Cite
|
Sign up to set email alerts
|

Delafloxacin: Place in Therapy and Review of Microbiologic, Clinical and Pharmacologic Properties

Abstract: Delafloxacin (formerly WQ-3034, ABT492, RX-3341) is a novel fluoroquinolone chemically distinct from currently marketed fluoroquinolones with the absence of a protonatable substituent conferring a weakly acidic character to the molecule. This property results in increased intracellular penetration and enhanced bactericidal activity under acidic conditions that characterize the infectious milieu at a number of sites. The enhanced potency and penetration in low pH environments contrast what has been observed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
80
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 56 publications
2
80
0
Order By: Relevance
“…It also has greater affinity for DNA gyrase that older fluoroquinolones [83], which contributes to it having MICs that are consistently three-to five-fold lower. These features mean that delafloxacin not only exhibits a broader spectrum of activity but also confers less resistance compared to other fluoroquinolones.…”
Section: Delafloxacinmentioning
confidence: 99%
“…It also has greater affinity for DNA gyrase that older fluoroquinolones [83], which contributes to it having MICs that are consistently three-to five-fold lower. These features mean that delafloxacin not only exhibits a broader spectrum of activity but also confers less resistance compared to other fluoroquinolones.…”
Section: Delafloxacinmentioning
confidence: 99%
“…In vivo pharmacokinetic and pharmacodynamic studies have demonstrated rapid oral absorption of delafloxacin, high bioavailability (60-70%), and renal excretion [19]. Delafloxacin is a concentration-dependent fluoroquinolone, exhibiting in vivo MICs of ≤ 1 mg/L against P. aeruginosa and 0.25 mg/L for Klebsiella pneumoniae, which predicts , minimum inhibitory concentration at which growth of 90% of organisms is inhibited, expressed in micrograms per milliliter (μg/ml), which were only calculated for microbes with more than 10 isolates efficacy against 75% and 78% of strains respectively [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have shown MIC levels for delafloxacin to be 3-5 times lower than other fluoroquinolones against Gram-positive microbes [21]. Additionally, multiple groups have shown its higher in vitro efficacy against Gram-positive organisms compared to other in-class agents [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, some available agents used to treat these MDR infections have limitations in their efficacy, spectra of activity, and side effect profile . Fortunately, the past years have produced several agents in the pipeline with novel moieties and a potential to overcome these obstacles …”
mentioning
confidence: 99%
“…6,7 Fortunately, the past years have produced several agents in the pipeline with novel moieties and a potential to overcome these obstacles. [8][9][10][11] Historically, tetracyclines (TET) have been used for the management of gram-negative skin and soft tissue and intraabdominal infections (IAI). 12 Although their use had been challenged with the onset of bacterial resistance, the development of new TET-like antibiotics, such as omadacycline and eravacycline (ERV), have the potential to overcome these challenges.…”
mentioning
confidence: 99%